(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A woman is the builder and moulder of a nation’s destiny. Though dedicate and soft, she has a heart far stronger and bolder than man. She is the supreme inspiration for man’s onward, an embodiment of peace, love, pity and compassion. Ostensibly the position occupied by women in a society determines the degree of development of that particular nation. Fireworks industry is one of the labour intensive industries in our country especially in South India. It mainly depends more upon women that men. Hence in this study an attempt is made by the researcher to study how far the women labourers involved in the fireworks industry are satisfied with their job. The present study has been undertaken with the primary objective of analyzing the factors influencing job satisfaction and opinion of women employees in fireworks industry. The investigation encompassed an extensive survey to obtain primary data from sample respondents of 114 employees in Sivakasi. The interview schedule covered all the details like personal data, factors like system of wage payment, bonus, advance , incentives etc., The data were collected using the investigation list which contained 25 phrases on Likert scale in order to measure the opinion of women employees.